Raised Cosine Interpolator Filter for Digital Magnetic Recording Channel. (9th March 2011) - Tsai, Hui-Feng; Jiang, Zang-Hao
Abstract : Interpolators have found widespread applications in communication systems such as multimedia. In this paper, the interpolated timing recovery employing raised cosine pulse for digital magnetic recording channel is investigated. This study indicates that the raised cosine interpolator with rolloff factorβ between 0.4 and 0.6 is shown to have less aliasing effect and achieve better MSE performance than other interpolators such as the sinc, polynomial, and MMSE interpolators with similar computational complexity. The superiority of the raised cosine interpolator over other interpolators is also demonstrated on the ME2PRIV recording channel through computer simulations. The main advantage of the raised cosine interpolator is that it is potentially simpler and can be fully digitally implemented.